Performance evaluation Innovative Modified Sand Filters with Biomass Integration for Effective Produced Water Treatment - Algathafi Eisay,; Azaldin Allafi,; Almabrouk Almabrouk,; Abdrabba Hassan,; Suleiman Abdelrahim, (AlQalam Journal of Medical and Applied Sciences, 2025)
This work has evaluated the efficiency of modified sand filters filled with biomass for the removal of chemical and physical contaminants from produced water. Also, this study aimed at designing, constructing, and evaluating a cost-effective modified sand filter was undertaken. The sand filter was modified with the addition of biomass (Sawdust SD), where the biomass formed the largest part of the filter media, which comprised of four layers. Cylindrical filters were constructed with PVC pipes 10.16 cm2 in diameter and 70 cm in length, with inner layers composed of sand, gravel, and biomass. The filters were fed with produced water (PW) contaminated, which was brought from the Messla field. The filtered water was collected in a graduated glass cylinder, after which the samples were taken for analysis. Results indicated the removal of up to 5.25 % total suspended solids, 20% turbidity, 65% apparent color, 68.67% total organic matter, 2.2% total dissolved salt, and conductivity. قيّم هذا العمل كفاءة مرشحات الرمل المعدلة المملوءة بالكتلة الحيوية في إزالة الملوثات الكيميائية والفيزيائية من المياه المُنتجة. كما هدفت هذه الدراسة إلى تصميم وبناء وتقييم مرشح رمل معدل فعال من حيث التكلفة. عُدِّل مرشح الرمل بإضافة الكتلة الحيوية (نشارة الخشب)، حيث شكلت الكتلة الحيوية الجزء الأكبر من وسط الترشيح، والذي يتكون من أربع طبقات. صُممت المرشحات الأسطوانية باستخدام أنابيب بلاستيكية بقطر 10.16 سم² وطول 70 سم، مع طبقات داخلية مكونة من الرمل والحصى والكتلة الحيوية. غُذِّيت المرشحات بالمياه المُنتجة الملوثة، والتي جُلبت من حقل مسلة. جُمعت المياه المُفلترة في أسطوانة زجاجية مُدرَّجة، ثم أُخذت العينات للتحليل. وأشارت النتائج إلى إزالة ما يصل إلى 5.25٪ من إجمالي المواد الصلبة العالقة، و20٪ من العكارة، و65٪ من اللون الظاهري، و68.67٪ من إجمالي المواد العضوية، و2.2٪ من إجمالي الأملاح المذابة، والتوصيل